Effects of drip irrigation and cropping on soil salinity, ionic composition and waxy corn production in a severely saline and calcareous and gypsiferous soil - Tan, Junli; Kang, Yaohu; Jiao, Yanping; Wan, Shuqin; Wang, Xina; Tian, Juncang; Erel, Ran; Ben-Gal, Alon (International Journal of Agricultural and Biological Engineering, 2023)
Drip technologies have been suggested as practical for irrigation under conditions of high salinity and for reclamation of saline soils. Drip irrigation triggered by soil water potential thresholds was applied to both reclaim a severely saline calcareous gypsiferous soil and irrigate a waxy corn crop (Zea mays L. sinesis Kulesh). However, there is a lack of knowledge on the sustainability of reclamation of saline soils with drip irrigation and the changes in soil salinity and salt ion composition during the amelioration process. Therefore, effects on soil salinity, its ionic composition, and on crop growth and yields were evaluated in an experiment conducted in the Yinchuan Plain, northwest China. Treatments included fields in their first to fourth years of the drip irrigation reclamation-cropping scheme and adjacent native, non-cropped or irrigated saline-sodic land as control. Yield of waxy corn increased and days of growth to maturity decreased as a function of time and reclamation management. The improvement in crop performance could be largely credited to the reduction of soil salinity and changes in salt composition under the drip-irrigated reclamation protocols. The drip irrigation regime created a region of low salinity proximal to the emitters conducive to germination and plant growth. Deleterious ions for crop growth such as Na+ and Cl- were reduced while Ca2+ and Mg2+ concentration increased, especially in the upper 40 cm of soil. After only a single season of drip-irrigated waxy corn production, both Cl-/SO42- ratios and sodium adsorption ratio (SAR) decreased dramatically. The results suggested that drip irrigation is an effective technology for reclamation of severely saline-affected soils, such as those widely distributed over the Ningxia Plain in China and that this or similar reclamation strategy could be appropriate for reclamation of other hard to manage calcareous and gypsiferous soils.Keywords: soil salinity, calcareous, gypsiferous, ion composition, leaching, salt transportDOI: 10.25165/j.ijabe.20231605.8125Citation: Tan J L, Kang Y H, Jiao Y P, Wan S Q, Wang X N, Tian J C, et al. Effects of drip irrigation and cropping on soil salinity, ionic composition and waxy corn production in a severely saline and calcareous and gypsiferous soil. Int J Agric & Biol Eng, 2023; 16(5): 142-154.